Visual inspection of MR relative cerebral blood volume maps has limited value for distinguishing progression from pseudoprogression in glioblastoma multiforme patients. (October 2017) - Kerkhof, Melissa; Tans, Pauline L; Hagenbeek, Rogier E; Lycklama à Nijeholt, Geert J; Holla, Finn K; Postma, Tjeerd J; Straathof, Chiara S; Dirven, Linda; Taphoorn, Martin JB; Vos, Maaike J
Aim: We examined whether visual interpretation of relative cerebral blood volume (rCBV) color maps made with dynamic susceptibility-weighted perfusion MRI can reliably distinguish progressive disease (PD) from pseudoprogression (PsPD) in glioblastoma patients during treatment with temozolomide chemoradiation.Materials & methods: Magnetic resonance (MR) perfusion-weighted images were evaluated based on visual inspection of rCBV maps. Sensitivity and specificity were calculated to assess if rCBV can reliably differentiate between PD and PsPD, during standard chemoradiation therapy.Results: Evaluation of dynamic susceptibility-weighted contrast-enhanced perfusion MRI by visual interpretation of rCBV maps did not differentiate PD from PsPD (sensitivity = 72%; specificity = 23%). Furthermore, the interpretation of the rCBV maps had no prognostic value regarding survival.Conclusion: Qualitative rCBV-based dynamic susceptibility-weighted contrast-enhanced perfusion MRI does not reliably differentiate PD from PsPD, and is not prognostic for survival in glioblastoma multiforme patients during treatment with temozolomide chemoradiation.